Meningkatkan Keterampilan Berpikir Kritis Muatan Matematika Menggunakan Kombinasi Model PBL, TTW, DAN CRH - Mahdinatul Khaira; Wahdah Refia Rafianti (GLOBAL SCIENTS PUBLISHER, 2026)
As an educator, determining the right learning model can improve the quality of learning interactions in the classroom. This study was conducted on fifth-grade students of SDN Kuin Utara 5 Banjarmasin which aims to evaluate the effect of implementing a combination of Problem-Based Learning, Think Talk Write, and Course Review Horay models on learning activities, critical thinking skills, and mathematics learning outcomes on the topic